Synthetic Life and the Value of Life - Persson, Erik (Frontiers in Bioengineering and Biotechnology, 2021)
If humans eventually attain the ability to create new life forms, how will it affect the value of life? This is one of several questions that can be sources of concern when discussing synthetic life, but is the concern justified? In an attempt to answer this question, I have analyzed some possible reasons why an ability to create synthetic life would threaten the value of life in general (that is, not just of the synthetic creations), to see if they really give us reason to worry. The main conclusion is that it is unlikely that a future human ability to create life will really have a great negative impact on these characteristics of life. It, therefore, seems unlikely that the value of life will be negatively affected by the ability to create synthetic life, though it is possible that the properties in question will be less salient in the synthetic life and thus that the value of the synthetic life will be lower than that of existing life, which in turn can lead to a disturbing difference in value between different kinds of life.